Catering to the Quiet and the Sociable A Proposal of Introversion and Extraversion as Emerging Market Segments - Bosonac, Ashley; Carissa Civitello (International Journal of Business and Social Science Research, 2024)
Target marketing leverages many human characteristics to persuade a specific consumer group best. These characteristics may include demographic, geographic, psychographic, and lifestyle traits. The psychographic factors considered in target marketing most commonly include an understanding of consumer values and behavior, not personality type. Few studies have analyzed how personality type, more specifically introversion and extraversion, might shape the outcome of a campaign. Introversion and extraversion have proven to have a pivotal role in other areas of business, such as the workplace, sales forces, and customer engagement. Drawing on that connection, this research hypothesized that these personality types might also impact consumer responses to a marketing campaign, particularly the promotional element. To answer these queries, multiple theories of personality were analyzed, including Jung’s Theory of Personality, and applied to previous research to introversion and extraversion in target marketing. Results reflected that there is considerable merit behind the pursuit of tailored advertisement campaigns that target introverts and extroverts respectively. Such strategies might increase metrics and create a more predictable and direct campaign. Subsequent research is suggested to further corroborate this conclusion.